Study of the Expansion of Cylindrical Elastic Tube with Uneven Opening under Constant Internal Pressure - Maharjan, Nischal; Subedi, Man Bahadur (Journal of the Institute of Engineering, 2020)
Our work is development of simplified model of elastic cylindrical tube by making several assumptions. We approximate tube walls to be thin but we do not neglect the stress exerted by the wall on the fluid inside. We also study expansion of such tubes under internal pressure and develop balance and kinematic equations of the model and then study kinematic properties of its deformation. We then modify Reynold's transport theorem and test its agreement with obtained results from the model. After that we perform further analysis for some of the results obtained.